Sociocultural Adjustment And Coping Strategies Of Korean And Japanese Students In A Thai International College - Rhein, Douglas (Penerbit Universiti Sains Malaysia (USM Press), 2018)
This study is devoted to understanding the adjustment issues Japanese and Korean international students face in Thai international higher education. An exploratory study of 15 visiting Korean college students and 15 visiting Japanese college students in Thai international programs was conducted using qualitative methods. A series of 30 face-to-face in-depth interviews regarding the participants’ sociocultural adjustment to their host community was conducted in 2015–2016. Participants responded to open-ended questions regarding their adjustment experiences and perceptions of the host culture. The interview data was thematically coded into several categories. Participants’ experiences were diverse and ranged from very subtle forms of discrimination and stereotyping to sexual harassment. The most frequently reported impediments to sociocultural adjustment included Thai language issues, excessive undesirable attention from the host community, academic adjustment, and diffculty establishing friendships with the host nationals. The most commonly reported coping strategies reported were the use of social support networks and social isolation from the host community. Implications for international relations departments and international programs within a Thai context are discussed.